Screen time is negatively associated with sleep quality and duration only in insufficiently active adolescents: A Brazilian cross-sectional school-based study - dos Santos, Amanda B. [UNESP]; Prado, Wagner L.; Tebar, William R. [UNESP]; Ingles, Jared; Ferrari, Gerson; Morelhão, Priscila K.; Borges, Luan O. [UNESP]; Ritti Dias, Raphael M.; Beretta, Victor S. [UNESP]; Christofaro, Diego G.D. [UNESP] (Elsevier, 2024)
Background: Time spent on screen devices affects sleep quality and duration leading to several health impairments in youth. Although physical activity (PA) benefits sleep patterns and decreases screen time in adolescents, it is unclear whether the relationship between sleep quality/duration and screen time could be influenced by PA levels. Objective: To analyze the association between sleep quality and duration with screen time in Brazilian adolescents according PA levels. Methods: The sample included 1010 adolescents aged 13.2 ± 2.4 years (n = 556 females − 55 % of the sample). Sleep quality and sleep duration, and PA were assessed by Mini Sleep and Baecke questionnaires, respectively. Participants in the highest quartile were classified as physically active. Screen time was analyzed by the self-reported number of hours spent on different screen devices (i.e., television, computer, videogame, and cellphone/tablet). Participants in the highest tertile were classified as having high screen time. Sex, age, and body mass index were considered covariates in binary logistic regression models. Results: Poor sleep quality was observed in 52.3 % of the sample, whereas 46.6 % reported sleeping less than eight hours/day. High screen time was associated with poor sleep quality (OR = 1.45; 95 %CI = 1.01–2.12) and insufficient sleep duration (OR = 1.52; 95 %CI = 1.01–2.03) in adolescents insufficiently active. There were no associations between screen time and sleep parameters in active adolescents. Conclusion: High screen time was associated with poor sleep quality and insufficient sleep duration only in insufficiently active adolescents. These results suggest that high PA levels may contribute to improving sleep patterns in pediatric population.
Keywords: Exercise; Sedentary behavior; Sleep quality; Television; Youth